2015
DOI: 10.1519/jpt.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Balance Training Program Using a Foam Rubber Pad in Community-Based Older Adults

Abstract: This study confirms that balance training in older adults performed using a foam rubber pad is effective for improving balance ability, and that this improvement occurs 2 months earlier compared with balance training performed on a stable surface. These findings suggest that balance training performed using a foam rubber pad is beneficial to clients and service providers because the programs improve physical functioning with a reduced number of exercise sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 45 publications
2
70
0
2
Order By: Relevance
“…The improvements in static and dynamic balance in this study were similar to those reported in previous studies with indoor clinical variable surface training, which has been demonstrated to provide various types of sensory information to improve proprioception and cutaneous receptor sensitivity [ 14 , 39 , 40 ]. This may explain why the fall prevention exercises on the outdoor multisurface terrain effectively improved balance abilities in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The improvements in static and dynamic balance in this study were similar to those reported in previous studies with indoor clinical variable surface training, which has been demonstrated to provide various types of sensory information to improve proprioception and cutaneous receptor sensitivity [ 14 , 39 , 40 ]. This may explain why the fall prevention exercises on the outdoor multisurface terrain effectively improved balance abilities in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that multisurface terrain, which is composed of variable surface characteristics, is a great challenge for older adults and can be exploited as a fall prevention intervention to reduce falls [ 13 ]. It has been shown that proprioception and cutaneous receptor sensitivity are significantly enhanced by exercise performed on unstable surfaces compared with exercise on stable surfaces [ 13 , 14 ]. Recent evidence estimates that plantar perception training on foam rubber of different levels of hardness significantly improves plantar perception, which is insensitive even in healthy old adults, to improve balance abilities [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The search returned 4006 records, of which 108 trials involving 23 407 participants were eligible for inclusion (figure 1). 18 The characteristics of the 108 included trials are summarised in online supplementary material B 10 19–125…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated an effect of balance training on other balance tasks that were not trained or other kinds of movements (Hirase, Inokuchi, Matsusaka, & Okita, 2014;Sayenko et al, 2010;Yavuzer et al, 2006). This difference of results could be due to different reasons.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%